Defect‐Engineered Graphene for High‐Energy‐ and High‐Power‐Density Supercapacitor Devices. Issue 33 (14th June 2016) - Zhu, Jingyi; Childress, Anthony S.; Karakaya, Mehmet; Dandeliya, Sushmita; Srivastava, Anurag; Lin, Ye; Rao, Apparao M.; Podila, Ramakrishna
Abstract : Defects are often written off as performance limiters . Contrary to this notion, it is shown that controlling the defect configuration in graphene is critical to overcome a fundamental limitation posed by quantum capacitance and opens new channels for ion diffusion. Defect‐engineered graphene flexible pouch capacitors with energy densities of 500% higher than the state‐of‐the‐art supercapacitors are demonstrated.